What’s next? Preparing for the Next Leadership Position - Markus Pomper; Margaret Thomas Evans (Academic Chairpersons Conference Proceedings, 2022)
Many department chairs eventually return to their faculty positions. However, for some of us the department chair position is a stepping stone for advancing to higher administrative ranks. This interactive session will provide suggestions on how to prepare for applying for leadership positions above the department chair.
Keywords: Transitioning roles; career changes; academic leadership